Quality characteristics and antioxidant activity of fermented symbiotic beverages supplemented with Eucheuma cottonii - Ali, Muhammad Qasim; Mohd Akmal, Azhar; Mimi Sakinah, Abdul Munaim; Nur Fathin, Ruslan; Nour, Abdurahman Hamid; Noormazlinah, Ahmad; Noman, Abeer Essam; Alsubhi, Luay M. (Springer Nature, 2025)
Seaweeds are an excellent source of nutrients and bioactive compounds associated with health benefits. In this study, symbiotic beverages were prepared by submerged fermentation with Lactobacillus and SCOBY as fermented materials and using Eucheuma Cottonii seaweed. During fermentation, the quality characteristics were analyzed and the physicochemical (pH, acidity, sugar, and alcohol content), Total phenolic content (TPC), Total flavonoid content (TFC), antioxidant capacity (DPPH, FRAP) organoleptic properties (9-point hedonic scale) of seaweed beverages. The pH levels of Lacto-based (5.2 ± 1.64) and SCOBY-based beverages reached (4.5 ± 0.12) and acidity for (0.5 ± 0.06) and (0.9 ± 0.07) after 30 days of fermentation. Sugar content decreased, and alcohol content increased with an increase in the number of fermentation days. The protein content increased significantly (p < 0.05) during fermentation. However, Lacto-based beverages have a low protein content, and SCOBY-based beverages have a high protein content (0.25 mg/ml). SCOBY-based seaweed beverages have high flavonoids (29.44 ± 0.63) and phenolic contents (27.44 ± 0.02). The DPPH value of Lacto-based beverages is (61.23 ± 1.54%), SCOBY-based beverages are (61.98 ± 0.22%), and the FRAP value is (17.53 ± 0.08%) and (19.98 ± 0.08%) after 30 days of fermentation. The heavy metal content in seaweed beverages was below the standard value; therefore, it is safe for consumption. The results showed that SCOBY-based beverages have enhanced nutritional and improved sensory properties, indicating the possibility of commercialization.